The compressive strength and static biodegradation rate of chitosan-gelatin limestone-based carbonate hydroxyapatite composite scaffold - Rianti, Devi; Purnamasari, Alqomariyah Eka; Putri, Rifayinqa Ruyani; Salsabilla, Noor Zain; Faradillah; Munadziroh, Elly; Agustantina, Titien Hary; Meizarini, Asti; Yuliati, Anita; Syahrom, Ardiyansyah (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: One of the main components in tissue engineering is the scaffold, which may serve as a medium to support cell and tissue growth. Scaffolds must have good compressive strength and controlled biodegradability to show biological activities while treating bone defects. This study uses Chitosan-gelatin (C–G) with good flexibility and elasticity and high-strength carbonate hydroxyapatite (CHA), which may be the ideal scaffold for tissue engineering. Purpose: To analyze the compressive strength and static biodegradation rate within various ratios of C–G and CHA (C–G:CHA) scaffold as a requirement for bone tissue engineering. Methods: The scaffold is synthesized from C–G:CHA with three ratio variations, which are 40:60, 30:70, and 20:80 (weight for weight [w/w]), made with a freeze-drying method. The compressive strengths are then tested. The biodegradation rate is tested by soaking the scaffold in simulated body fluid for 1, 3, 7, 14, and 21 days. Data are analyzed with a one-way ANOVA parametric test. Results: The compressive strength of each ratio of C–G:CHA scaffold 40:60 (w/w), 30:70 (w/w), and 20:80 (w/w), consecutively, are 4.2 Megapascals (MPa), 3.3 MPa, 2.2 MPa, and there are no significant differences with the p= 0.069 (p>0.05). The static biodegradation percentage after 21 days on each ratio variation of C–G:CHA scaffold 40:60 (w/w), 30:70 (w/w), and 20:80 (w/w) is 25.98%, 24.67%, and 20.64%. One-way ANOVA Welch test shows the result of the p-value as p<0.05. Conclusion: The compressive strength and static biodegradation of the C–G:CHA scaffold with ratio variations of 40:60 (w/w), 30:70 (w/w), and 20:80(w/w) fulfilled the requirements as a scaffold for bone tissue engineering.